Industry Required Competencies as Predictors of Graduates’ Employability - Dorado, Leonardo B. (11th International Scholars Conference, 2018)
This study primarily focused on understanding the required competencies of the industry for our graduates and the factors that predict employability of graduates. It answered the following objectives: a) determine the competencies required by companies in hiring new graduate students and graduates with one-year experience; b) find out difference in competencies that predict employability of graduates when new and one year graduates were compared. This research utilized descriptive methods and used purposive sampling in the selections of 32 participants who are supervisors and human resource managers that were responsible for hiring and selection of employees within the CALABARZON area (Region IV-A). The study utilized CHED Memorandum Order No. 20, series of 2015 (CMO) and Graduate Employability Indicators (GEI) Employers Survey by the Australia Learning and Teaching Council as the basis in the development of questionnaire. The participants answered the validated survey questionnaire to generate the findings of this study. The data gathered were tallied and interpreted through a statistical tool and utilized mean score, t test and Pearson r. The findings showed that employers expect new graduates to must have competencies such as: computing professionalism & ethics; communication; and individual and team work; work attitude; and work spirit. While competencies that predict employability of graduates are working quality; working attitude; working spirit; and working efficiency. The study implied the necessity to look at the alignment of curriculum that would produce competencies among graduates. It is recommended to increase the number of participants and involve more stakeholders in the enhancement of the curriculum.